(3TQM QSGdI GdGSJYGQI ddCfWGcjs - (3bQg JHg dj, MSjf Hf eUWai GdBjOjfj, J(B1191(3g`s ((3edG eUWai Hf CMeOs)
(3ChdgG (B:s
(3GdMeO def CaQO GdMbGFb Ydi ef QTM HCYdi GdObGFbhHYO ajbhdGHf bQg(B"(3Ef QSGdI GdGSJYGQI ddehdieMehO GdCfWGcjdeG cGfJ eMJhjICQOJ Cf CaVdgGs
(3BNQgG (B:s
(3CYde Cfge bO CWjYhG Ydi Cf GdeLGR hGdcfGjI CHdZ ef GdMbjbI hGdJUQjM dchfgG cOYh GdTjA HHjfIhdfNJe GdcdGe HGdMeO ddg SHMGf QHc QH GdYRI YeG jUahf hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: 1 / 644s
(3gOjI GdYGQajf(B: 1 / 327s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdHdGZIs